Ethnobotany of Medicinal Plants in Semendo Tribe of Buay Pemaca District - Ulmillah, Aulia; Widiani, Nurhaida; Mardiyanti (LenteraBio : Berkala Ilmiah Biologi, 2025)
The abundant diversity of medicinal plants provides benefits to the community in Buay Pemaca Subdistrict, South Ogan Komering Ulu Regency. The people in this subdistrict utilize these plants as traditional medicine to treat various diseases. This study aims to explore traditional medicine knowledge and practices, including the identification of medicinal plant species, the plant parts used, as well as the processing and utilization of medicinal plants in traditional remedies. The approach used in this study was qualitative with descriptive analysis. Data were collected through observations, interviews with 30 informants consisting of 5 key informants (traditional healers) and 25 non-key informants (community members), as well as documentation. The types of interviews used in this study were semi-structured interviews and in-depth interviews. The sampling technique employed was purposive sampling and snowball sampling. Data were analyzed using the Index of Cultural Significance (ICS), Sum of Use-Value (SUV), and Fidelity Level (FL). The research findings were then analyzed descriptively. The results of the study revealed that 19 plant species from 13 families are utilized by the local community as traditional medicine. The most commonly used plant parts are leaves, followed by rhizomes, fruits, and stem bark. The utilization of these plant parts is carried out in various ways, including boiling, pounding, cutting into small pieces, grating, extracting sap, or even applying it directly to wounds.